The level of psychological pressure faced by married working women in the southern governorates of the West Bank in the territories of the Palestinian National Authority - شحاده عامر صابر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study aimed to identify the level of psychological stress experienced by working women in the Bethlehem Governorate. The study sample included a group of respondents from a sample available through social media due to the difficulty of movement in the occupied Palestinian territories. The study sample consisted of 302 respondents from private and government sectors. Participants responded to a psychological stress scale, which was developed by the researcher. The scale’s apparent validity was verified by a group of specialists, and Cronbach’s alpha was used to determine the reliability of the instrument. The descriptive analytical approach was used in this study due to its suitability for the study’s purposes. The statistical package SPSS was used to analyze the data. The results showed higher psychological stress among working women with children under the age of 10 compared to women with children over 10 years old, as well as among women who work shifts compared to women with regular work hours. The researcher made several recommendations, including: Pay attention to the mental health of working women and help them adapt to the Palestinian reality, which is fraught with various economic, social, academic, and familial pressures. Conduct training programs for working women to develop skills to cope with psychological stress.